Prognostic role of serum ammonia in patients with sepsis-associated encephalopathy without hepatic failure - Zhao, Lina; Hou, Shaowei; Na, Risu; Liu, Bin; Wang, Zhiwei; Li, Yun; Xie, Keliang (Frontiers in Public Health, 2023)
Abstract Objectives: Our previous study shows that serum ammonia in patients without hepatic failure is associated with a poor prognosis in patients with sepsis. The relationship between serum ammonia in patients without hepatic failure and the prognosis of sepsis-associated encephalopathy (SAE) remainsunclear. We aimed to explore the prognosis of patients with serum ammonia without hepatic failure and SAE. Material and Methods: We collected 465 patients with SAE admitted to the intensive care unit (ICU) from Medical Information Mart for Intensive Care IV (MIMIC IV) from 2008 to 2019. SAE patients were divided into survival group(369 patients) and non-survival group(96 patients). We used the Wilcoxon signed-rank test and Multivariate Logistic regression analysis to analyze the relationship between serum ammonia levels and the prognosis of SAE patients. The R software was used to analyse the dataset. Results: The mortality of patients with SAE is 20.6%. The Simplified acute physiology score (SAPS II) and Charlson are independent risk factors for death in patients with SAE. Although serum ammonia in patients without hepatic failure is not significantly associated with SAE mortality, longer hospital stays, and higher SAPS II score, Charlson, lower Glasgow coma scale (GCS), is associated with higher sequential organ failure assessment (SOFA) scores and lactate levels in SAE patients. Conclusions: Serum ammonia in patients without hepatic failure is associated with higher SOFA scores and lactate levels in SAE patients. SAPS II and Charlson can be used to assess the prognosis of SAE patients. We should closely monitor the levels of serum ammonia, SAPS II, and Charlson in SAE patients.